Criminal Law, Pshychology and Corruption Offenses. Interview with Carolina Lizárraga Houghton - Themis, Revista (2015)
Is corruption a circumstantial problem or is it really rooted in the Peruvian society? Why does Criminal Law should take action against corrupt acts? How is corruption perceived from the point of view of the Peruvian Judicial Power?These and other issues are answered by the interviewed, from her experience as judge and as officer in charge of the fight against corruption in Peru.